PERAN GURU AKIDAH AKHLAK DALAM MEMBENTUK MOTIVASI BERPRESTASI SISWA KELAS VIII DI MTS ALWASHLIYAH SELAT BESAR LABUHANBATU - Asrani Lubis; Pan Su’aidi; Yulia Warda (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to describe and analyze the strategic role of Akidah Akhlak teachers in fostering achievement motivation among grade VIII students at MTs Alwashliyah Selat Besar, Labuhanbatu. This research employs a qualitative descriptive approach with a field research design. Data were collected through in-depth interviews, participant observation, and documentation studies. The primary informants included Akidah Akhlak teachers and grade VIII students, selected through purposive sampling. Data analysis followed the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing, with triangulation used to ensure data validity. The findings indicate that Akidah Akhlak teachers play a multifaceted role as motivators, role models (uswah hasanah), and counselors. Teachers internalize the value of fastabiqul khairat (competing in goodness) and the doctrine of